Cybercrime In The Philippines: A Case Study Of National Security - Jia Li, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Transformations in technology that have impacted the global economy have ushered in an information and communication technology-led revolution. This global shift has paved the way for what many has described as “a borderless world” that has led to new ways of doing things in both the private and public sector of a nation in today’s modern times. The concept of E-service (short for electronic service) which is the hallmark of this technology represents an application that utilizes the use of information and communication mediated technologies for the facilitation of the delivery of a varied scope of services or aptly called “electronic services”. In the public sector, E-service enable public agencies who are the service providers achieve enhanced administration in delivering services for citizens or the public. This allows the flow and process of information for all stakeholders to be processed efficiently. In the private sector, applications of e-commerce are continually affecting trends and prospects for business over the internet. E-commerce in the country encourages shifts from traditional modes of doing business to electronic alternatives, thereby enhancing the processing of business transactions. Its benefits are limitless, from expanded geographic reach, easy access to information, marketing and advertising visibility and cost reduction which all bottom lines to increase revenues. Security is the challenge that faces the implementation of e-services in a country in the country where such implementation is crucial to the delivery of basic services to the populace. Without a guarantee of privacy and security for information circulating in the internet, e-services will fail. The menace of the proliferation of cyber crime activities hampers the reach of e-government and compromises the achievement of its national goals in creating enhanced socio-economic environment for its citizens. In essence, it is tantamount to becoming a grave threat to national security. This paper sought to present how cyber crime has impacted areas of both the public and private sector here in the Philippines that threaten national security of its citizens. It presented among others, a profile of cyber criminals including their tools and motives, the modes and manner on how different cyber crimes are being committed and the implications to specific stakeholders most vulnerable. In view of the results, recognizing the national economic implications of cyber threats, this paper concludes that the implications of cybercrime in the Philippines are of an impending grave nature which threatens that national security of its people, its private sector and its government.